Loss of PI3K blocks cell-cycle progression in a Drosophila tumor model. - Willecke, M.; Toggweiler, J.; Basler, K. (Oncogene, 2011)
Tumorigenesis is a complex process, which requires alterations in several tumor suppressor or oncogenes. Here, we use a Drosophila tumor model to identify genes, which are specifically required for tumor growth. We found that reduction of phosphoinositide 3-kinase (PI3K) activity resulted in very small tumors while only slightly affecting growth of wild-type tissue. The observed inhibition on tumor growth occurred at the level of cell-cycle progression. We conclude that tumor cells become dependent on PI3K function and that reduction of PI3K activity synthetically interferes with tumor growth. The results presented here broaden our insights into the intricate mechanisms underling tumorigenesis and illustrate the power of Drosophila genetics in revealing weak points of tumor progression.